Dampak Guncangan Indikator Sosial-Ekonomi terhadap Migrasi Neto di Indonesia Tahun 1991-2023: Pendekatan Vector Error Correction Model (VECM) - Sarwosih, Arifa Tri; Pratama, Muhammad Zacky Arie; Nabilah, Yasmin Nur Alya; Kartiasih, Fitri (Politeknik Statistika STIS, 2025)
Migration plays an important role in shaping socio-economic dynamics across provinces in Indonesia. This study aims to analyze the impact of shocks in socio-economic indicators—namely the Open Unemployment Rate (OUR) and inflation—on net migration during the period 1990–2022. Annual data from Statistics Indonesia (BPS) is analyzed using the Vector Error Correction Model (VECM) approach. The results show that net migration responds dynamically to socio-economic shocks, with system stability reached around the 30th year. Shocks to the unemployment rate have a more dominant long-term impact compared to inflation. The Variance Decomposition Analysis (VDA) confirms the relatively greater contribution of OUR to the variability of net migration. These findings support the push-pull theory of migration and fill a gap in national-level empirical studies. Policymakers need to design adaptive responses to shocks in unemployment and inflation to reduce migration pressures and promote balanced regional development.